PHENOMENOLOGY OF THE PROTEST ACTIVISM: REMINISCENCES OF "GREAT REFUSAL" - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article examines the protest form of individual and mass mentality in conditions of social anomie. The author retrospectively turns to the philosophical reflections of ancient cynicism and the Critical Theory of Society, which are based on the ideas of the «Great Refusal», as well as to the practical experience of protesting in Ukrainian realities.